Phosphorus response and mineral composition of Ethiopian highland Trifolium (clover) species - Nnadi, L.A.; Haque, I.; Mugwira, L.M. (Informa UK Limited, 1993)
Pot trials and laboratory phosphorus (P) sorption studies were conducted to evaluate the response of seven Ethiopian clover species (T. decorum, T. steudneri, T. quartinianum, T. rueppellianum, T. schimperi, T. tembense, and T. subterraneum) to applied P and further to determine the critical external P requirements of these legumes. Application of P fertilizer increased the dry matter yield, N, and P contents of all species, and P and N use efficiency in T. steudneri. Maximum dry matter yields were attained between 20 and 40 kg p/ha. At zero P application, T. decorum gave the highest dry matter yield, indication that this species can thrive better than the others on soils of low available The external P requirements of the species ranged from 0.003 to 0.025 mg/L on a low P - fixing soil, and 0.0004 to 0.0019 mg P/L on a high P-fixing soil. These results suggest that the fertilizer requirements of crop species may not be based on a single P sorption curve if the soils have widely different P sorption characteristics.